Post-Brexit realism and international law: Renegotiating a bad Withdrawal Agreement - Patrick Minford (Cardiff University, Cardiff Business School, 2019)
Some pro-Brexit MPs will not vote for the government's proposed Withdrawal Agreement because of its fine print: they think it will be written in indelible tablets of law that we can never change. But they forget that sovereign states will not indefinitely stay in treaties that do not suit them, if no one can force them to, as in general no one can, unlike in national law where the state can force us. That is just the plain economics of national self-interest, as deployed in game theory studies of international treaties. Our Agreement with the EU if we sign it will not last for long if it stops us from pursuing our interests in trade and regulation: no one, certainly not the EU, can force us to stay with it. It has been negotiated like a hostile divorce because the EU wanted to prove it does not pay to leave. But once the divorce has happened, it will be a new situation where, as with ex-partners in a divorce, they will want to live harmoniously with us in the long term. There will be sensible diplomacy so that we can accommodate each other's interests, in a process of adaptation. After leaving, we can push ahead with good policies on trade, regulation and migration that the government we vote for will pursue; the EU will cooperate as it will not wish us to move to default WTO rules.
Keywords: 330